2009
DOI: 10.1080/09512740903127978
|View full text |Cite
|
Sign up to set email alerts
|

Social movements and political opposition in contemporary Thailand

Abstract: There is an underlying optimism in much of the literature that considers the emergence of social movements as being associated with deepening processes of democratization. The expansion of civil society is seen to expand political space. This paper takes a critical lens to this perspective, using recent political events in Thailand as a case study of the political strategies and alliances of social movements. We examine the debates that saw many social movements and their leaderships initially support elected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Several NGOs expected to be appointed to the Senate (Giles Ji, 2009;Kengkij and Hewison, 2009;Pye and Schaffar, 2008). 10 Assuming the budget allows for the necessary outlays, these problems may be overcome within a couple of years (Bangkok Post, 9 April 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Several NGOs expected to be appointed to the Senate (Giles Ji, 2009;Kengkij and Hewison, 2009;Pye and Schaffar, 2008). 10 Assuming the budget allows for the necessary outlays, these problems may be overcome within a couple of years (Bangkok Post, 9 April 2006).…”
Section: Resultsmentioning
confidence: 99%
“…I cannot do justice to the details of the current Thai conflict -which many authors have outlined elsewhere (see Chairat, 2009;Connors and Hewison, 2008;Glassman, 2009;Glassman, 2010;Glassman et al, 2008;Kengkij and Hewison, 2009;Pasuk and Baker, 2009;Ungpakorn, 2010) -but I can summarise the two broad layers of conflict that all observers agree lie at the centre of the current crisis. One layer of the conflict is an inter-elite struggle between groups characterised as royalists and groups characterised as supporters of deposed Prime Minister Thaksin Shinawatra.…”
Section: Cracking Royalist Hegemonymentioning
confidence: 94%
“…In recent years, most scholars on this subject have focused on two main dimensions of the formal involvement of civil society leaders in political institutions. First, some observers have demonstrated how NGOs and their activists have been co-opted by the state and its various actors (Petras 1999;Kitirianglarp and Hewison 2009). In a particularly striking case study, Kim has analysed the engagement of South Korean NGOs in formal politics and found that the former are now ''disgraced with the stigma of over-politicisation'' (Kim 2009, 892).…”
Section: Pro-democracy Activists and Party Politics In Post-suharto Imentioning
confidence: 97%